Modularisierung in der Prozessindustrie: Bericht von der ACHEMA 2018. Issue 12 (5th November 2018) - Fasel, Henrik; Bruns, Bastian; Riese, Julia; Lier, Stefan; Grünewald, Marcus
Abstract: At ACHEMA 2018, various exhibitors from various areas of process engineering were asked about their general understanding of the term modularization. In particular, they were asked whether and how their company already integrates modularization in their various business areas. The interviews showed that among the companies surveyed there is a better understanding of modularization than expected. Nevertheless, it turned out that this understanding differs depending on the company's business area. Some exhibitors already use modularization in their product portfolios, e.g., in the construction of modular apparatus or production plants.